Islamic Religious Education in Responding to the Development of Science and Artificial Intelligence: Curriculum Analysis and Its Implications for the Formation of Students' Digital Morals - Muhammad Ridhoni Al Arif; Muhammad Zuhdi; Bobi Erno Rusadi (STIT Attaqwa, 2025)
The development of science and artificial intelligence (AI) has brought fundamental changes in the way humans learn, work, and interact. This transformation has not only impacted the technical aspects of education, but has also raised increasingly complex ethical, moral, and humanitarian issues. In this context, Islamic Religious Education (IRE) has a strategic role in guiding students to be able to deal with technological developments critically, ethically, and responsibly. This article aims to analyze the role and relevance of the Islamic Religious Education curriculum in responding to developments in science and artificial intelligence as part of contemporary global issues. This study uses the library research method by reviewing Islamic education literature, national curriculum policies, and relevant national journal research results. The results of the study show that the PAI curriculum needs to be developed contextually by integrating Islamic values, digital ethics, and critical awareness of technology. Islamic Religious Education is not positioned as a discipline that rejects science and AI, but rather as a foundation of values that guides the use of technology to remain on the side of humanity and benefit. Thus, Islamic Religious Education contributes significantly to the formation of digital ethics and moral responsibility of students in the era of artificial intelligence.